Revitalizing the Branding of Tegal City As the Japanese of Indonesia (Jurnal Bina Praja, 2023)
The researchers are revitalizing the branding of Tegal City as the Japanese of Indonesia through strengthening metal industrialization by networking with the manufacturing industry. This policy was carried out because of the potential for a home industry-based metal industry. This potential can undoubtedly become a brand that has long been owned by Tegal City but needs more touch and attention from the government. The researchers adopted a dual case study strategy with an exploratory qualitative approach as our research strategy. The discussion obtained from this research is the need for a link and match between the home metal and manufacturing industries. Even though there has been direct contact, the productivity of the home metal industry could have been better. In conclusion, we are revitalizing the branding of Tegal city as Japan Indonesia requires an injection of investors, quality human resource training to meet the demands of the manufacturing industry, and modernization of machines to increase the productivity of the home metal industry players.